Formation of raspberry like cobalt particles with hydrazine reduction in a polyol route - Khe, C.S. (American Institute of Physics Inc., 2016)
This work describes the effect of hydrazine hydrate on the formation of the raspberry-like morphology of the cobalt nanomaterials in a polyol route. In the synthesis, the molar ratio of N2H4 to Co2+was varied from 2.5 to 10. At the beginning with low molar ratio, spherical microspheres were formed. When the molar ratio was increased to 5 and above, final morphology of the cobalt nanomaterials became raspberry-like. This might be attributed to the absorption of the hydrazine complex of cobalt nanoparticles at certain facets during their growth stage and later self-assembled into the raspberry shaped microparticles. The plausible formation mechanism were proposed. Â© 2016 Author(s).